PAROXYSMAL TONIC UPGAZE MIMICKING INFANTILE SEIZURE - Akyol, Fatime; Ağ, Zehra Nur; Kırık, Serkan (Ankara Yildirim Beyazit University, 2023)
Non-epileptic paroxysmal events are very important in daily clinical practice. Paroxysmal tonic upgaze is a rare neuro-ophthalmologic non-epileptic paroxysmal condition characterized by episodes of continuous conjugated upward deviation of the eyes and normal horizontal gaze. Its pathogenesis is unknown, and its etiology is heterogeneous. The prognosis is often benign, but it's often confused with epilepsy. We present a case of "paroxysmal tonic upgaze" with a benign clinical course and spontaneous remission. © Annals of Translational Medicine. All rights reserved.
Keywords: non-epileptic; paroxysmal tonic upgaze; Pediatric